2016
DOI: 10.3748/wjg.v22.i48.10523
|View full text |Cite
|
Sign up to set email alerts
|

Gastric adenocarcinoma of the fundic gland (chief cell-predominant type): A review of endoscopic and clinicopathological features

Abstract: Gastric adenocarcinoma of the fundic gland (chief cell-predominant type, GA-FG-CCP) is a rare variant of well-differentiated adenocarcinoma, and has been proposed to be a novel disease entity. GA-FG-CCP originates from the gastric mucosa of the fundic gland region without chronic gastritis or intestinal metaplasia. The majority of GA-FG-CCPs exhibit either a submucosal tumor-like superficial elevated shape or a flat shape on macroscopic examination. Narrow-band imaging with endoscopic magnification may reveal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
52
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 24 publications
2
52
0
Order By: Relevance
“…According to Ueyama et al[ 10 ], endoscopic properties of GA-FG include no intestinal metaplasia or atrophic change in the surrounding mucosa, faded or whitish color, submucosal tumor shape with a soft appearance, and dilated vessels with branching architecture. Although the pathogenesis of GA-FG is unclear, GA-FG tends to arise from the normal gastric mucosa of the fundic gland region without atrophic change or intestinal metaplasia[ 2 ]. Therefore, H. pylori infection is not considered to contribute to the development of GA-FG, unlike for the regular histological type of gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Ueyama et al[ 10 ], endoscopic properties of GA-FG include no intestinal metaplasia or atrophic change in the surrounding mucosa, faded or whitish color, submucosal tumor shape with a soft appearance, and dilated vessels with branching architecture. Although the pathogenesis of GA-FG is unclear, GA-FG tends to arise from the normal gastric mucosa of the fundic gland region without atrophic change or intestinal metaplasia[ 2 ]. Therefore, H. pylori infection is not considered to contribute to the development of GA-FG, unlike for the regular histological type of gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Until recently, GA-FG has been recognized as cancer arising from gastric mucosa without atrophic change[ 2 ]. However, cases of GA-FG arising from gastric mucosa with atrophic change have now been reported[ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously published reviews showed that the average tumor diameter was 7.5 mm. Approximately 80% of all tumors were less than 10 mm in diameter at the time of diagnosis 6 and the diameter of the largest reported tumor was 85 mm 8 . Our observations were consistent with those of previous reports (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…The histological appearance of GA-FG is often that of a well-differentiated neoplasm, with a tumor-bearing resemblance to that of the fundic glands. Furthermore, at low magni cation, GA-FG, especially of the mixed cell type, can mimic a fundic gland polyp or a pyloric gland neoplasm 6 . It is necessary to differentiate GA-FG from fundic gland adenoma when a subset of GA-FG lacks the ability to invade or metastasize 4 .…”
Section: Introductionmentioning
confidence: 99%